Livestock, leopards and brown hyaenas: conflicts of cohabitation in the Roodewalshoek Conservancy, Mpumalanga - Van As, Michelle (University of the Free State, 2012)
Conflict between livestock farmers and predators has been an ongoing battle since the breeding of domestic animals were first attempted by man. Insufficient data on the dynamics of predators, especially in regions outside formal protected areas where they are perceived as problem animals, make control methods almost impossible. Due to complaints of predation by cattle farmers in the unspoiled Roodewalshoek Conservancy, the dynamics of livestock predation was investigated. Specific emphasis was placed on the relationship between the ecological traits of leopard, brown hyaena and natural prey species and the consequences thereof on livestock losses. Investigations were carried out by means of motion-sensing camera traps, combined with seasonal field observations of all physical signs of animals. The presence of recorded prey species showed a monthly variation, with some prey species present all year round while others showed definite periods of occurrence. Rainfall seemed to have some influence on the occurrence of such species. Most small potential prey species was observed continuously during the winter months and only sporadically during the summer. Medium sized potential prey species that occurred on a constant basis throughout the year in the study area included bushbuck, Chacma baboons and common grey duikers. Sporadic occurrence of impala and mountain reedbuck were encountered mostly during the mid-summer months, especially during December. All species classified as large prey were continuously present throughout the year, except for the aardvark which showed a sporadic presence and were mostly observed during mid-summer. Large predators were continually observed in the conservancy except in late summer during the month of January and reached highest numbers during early autumn, mid-winter and in the height of summer. All the other predators, including small and medium-sized predators, were present on a frequent basis except during late summer and only reached a high in mid-winter and early spring. It was also evident that, when the presence of large predators in the study area increased, the presence of other predators diminished. The majority of calves (59%) were killed by predators during the wet summer months, while only 41% of calves were predated upon during winter months with low precipitation. Lunar cycles seem to play a distinctive role in livestock predation with almost two thirds of calves lost to predators when moonlight intensity was low. Even though sufficient occurrences of natural prey could be found in the Roodewalshoek Conservancy, predation on livestock persists during the calving season. Regarding the key predator of livestock in the conservancy, both leopards and brown hyaenas were almost equally accountable and displayed alternating periods of calf predation. Instances of predation where the problem animal could be identified, implicated brown hyaenas in 48% and leopards in 52% of livestock losses. During times when brown hyaenas were responsible for the most calf losses, predation caused by leopards was low. High incidences of leopard predation consequently resulted in lowered brown hyaena predation. This could be due to inter-predator competition for shared resources. The behaviour of surplus-killing by both predator species is indicative of the ability to fully exploit all the available resources in their area. The relatively large number of livestock lost to predation each year may be due to a combination of several factors. These include the lack of predator control in adjacent game farms and other protected areas, continuous presence of livestock, leopards and brown hyaenas as well as the open, unattended system in which livestock is kept in the Roodewalshoek Conservancy.

Die situasie van konflik tussen vee-boere en predatore bestaan sedert die onstaan van die mak-maak van huisdiere en vee. Onvoldoende inligting aangaande die dinamika van predatore, veral dié buite die grense van bewaarde gebiede, bemoeilik die beheer-metodes van hierdie diere in areas van konflik. As gevolg van gereelde klagtes deur vleisbees-boere in die Roodewalshoek Bewarea, is die dinamika van vee-predasie in hierdie area ondersoek. Spesifieke klem is geplaas op die verwantskap tussen die ekologiese eienskappe van luiperds, bruin hiënas en natuurlike prooi-spesies, en die invloed hiervan op vee-verliese is ondersoek. Data-insameling is met behulp van beweging-sensitiewe kamera lokvalle, tesame met seisoenale veld observasies uitgevoer, ten einde alle fisiese teenwoordigheid van hierdie diere aan te teken. Die maandelikse teenwoordigheid van aangetekende prooi-spesies het variasie getoon, met sommige prooi-spesies aaneenlopend deur die hele jaar teenwoording terwyl ander opvallende periodes van afwesigheid getoon het. Dit blyk asof reënval ‘n invloed op die verspreiding van hierdie spesies het en die meerderheid van potensiële prooi-spesies is aaneenlopend tydens winter-maande en sporadies gedurende die somer waargeneem. Potensiële prooi-spesies van medium-grootte wat deurlopend in die studie-area teenwoordig was sluit die bosbok, bobbejaan en gewone duiker in. Sporadiese teenwordigheid van rooibokke en rooiribbokke is gedurende hoog-somer, veral tydens Desember, waargeneem. Alle spesies geklassifiseerd as groot prooi was heel-jaar teenwoordig, uitsluitend die erdvark wat sporadies in mid-somer teenwoordig was. Groot roofdiere was deurlopend oor die hele jaar, uitsluitend laat-somer in Januarie, in die bewarea teenwoordig. Die meerderheid waarnemings was egter tydens vroeg-herfs, mid-winter en hoog-somer. Alle ander predatore, dié van klein en medium- grootte, was aaneenlopend teenwoordig, behalwe tydens laat-somer. Die meerderheid van hierdie predatore is gedurende die middel van die winter asook vroeg in die lente waargeneem. Dit was ook duidelik dat, soos die teenwoordigheid van groot predatore in die studie-area toeneem, die teenwoordigheid van alle ander predatore afneem. Die meerderheid kalwers (59%) is tydens die nat somer-maande gevang, terwyl slegs 41% van kalf-verliese tydens droë winter-maande plaasgevind het. Die maan-siklus blyk ‘n bepalende rol in die predasie op vee te speel, met ongeveer twee-derdes van kalwers gevang tydens lae maanlig-intensiteit. Alhoewel genoegsame natuurlike prooi-diere in die Roodewalshoek Bewarea gevind kan word, duur predasie op kalwers gedurende die kalf-seisoen voort. Beide luiperds en bruin hiënas is ewe veel te blameer vir vee-verliese in die bewarea en dié roofdiere het afwisselende tydperke van predasie getoon. Gevalle waartydens die probleem-dier wel geïdentifiseer kon word, het getoon dat bruin hiënas vir 48% en luiperds vir 52% van vee-verliese verantwoordelik was. Periodes waartydens bruin hiënas vir die meerderheid verliese verantwoordelik was, het kalf- predasie deur luiperds afgeneem. Daarteenoor het hoë vlakke van kalf-predasie deur luiperds tot ‘n verlaging in kalf-predasie deur bruin hiënas gelei. Die rede hiervoor kan inter-predator kompetisie om dieselfde hulpbronne tussen hierdie diere wees. Veelvuldige doodmaak van prooi deur beide groot roofdiere dui op ‘n vermoë tot die volledige benutting van om alle beskikbare hulpbronne in hul area. Die substansiële jaarlikse vee-verliese as gevolg van predasie mag die resultaat wees van verskeie faktore. Hierdie faktore sluit in die tekort aan predator-beheer in die omliggende bewaarde gebiede, asook die aaneenlopende teenwoordigheid van beeste en luiperds en bruin hiënas. Tesame met die oop, onbewaakte sisteem waarin beeste in die Roodewalshoek Bewarea gehou word is dit nie verbasend dat ‘n konflik-situasie in hierdie area ontstaan het nie.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2012
Keywords: Predation (Biology); Animal behavior -- South Africa -- Mpumalanga; Animal communities -- South Africa -- Mpumalanga; Livestock -- Predators of; Leopard -- Behavior; Brown hyena -- Behavior